Synchronisation in open quantum systems - Davis-Tilley, Claire (2018)
Synchronisation has been explored extensively for classical systems from the mid-1600s, and is a phenomenon widely understood in many diverse systems. In the age of technology miniaturisation, there are great incentives to develop an understanding of quantum synchronisation, where quantum fluctuations become the dominant source of noise and non-classical features become important. This thesis considers different types of synchronisation in systems that can display highly non-linear, quantum behaviours. Phase synchronisation for a micromaser coupled to an external drive is initially considered, and it is found that for low photon numbers a semiclassical approximation underestimates phase synchronisation, but a perturbation theory can be accurate for sufficiently weak coupling in either a quantum or semiclassical regime. When a small detuning between the drive and micromaser is introduced, frequency entrainment is also found to exist.